Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª Ma; Abdelly, Chedly; Jorrín-novo, Jesús (Plant Physiology and Biochemistry, 2013)
Phytophthora cinnamomi is one of the agents that trigger the decline syndrome in Quercus spp., this being a serious threat to Mediterranean Holm oak forest sustainability and reforestation programs. Quercus ilex responses to Phytophthora cinnamomi have been studied in one-year olds seedlings from two Andalucía provenances, assessing the physiological water status and photosynthesis-related parameters. Upon inoculation with mycelium a reduction in water content, chlorophyll fluorescence, stomatal conductance and gas exchange was observed along a 90 days post inoculation period in both provenances. The reduction was higher in the most susceptible (SSA) provenance, than in the most tolerant (PCO), being these typical plant responses to drought stress. Leaf protein profiles were analyzed in non-inoculated and inoculated seedlings from the two provenances by using a 2-DE coupled to MS proteomics strategy. Ninety seven proteins changing in abundance in response to the inoculation were successfully identified after MALDI–TOF–TOF analyses. The largest group of variable identified proteins were chloroplasts ones, and they were involved in the photosynthesis, Calvin cycle and carbohydrate metabolism. It was noted that a general tendency was a decrease in the protein abundance as a consequence of the inoculation, being it less accused in the least susceptible, the Northern provenance (PCO), than in the most susceptible, the Southern provenance (SSA). This trend is clearly manifested in photosynthesis, amino acid metabolism and stress/defence proteins. On the contrary, some proteins related to starch biosynthesis, glycolysis and stress related peroxiredoxin showed an increase upon inoculation. These changes in protein abundance were correlated to the estimated physiological parameters and have been frequently observed in plants subjected to drought stress.
From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)
Keywords: Gene Expression Regulation; Holm oak decline; Holm oak proteomics; Phytophthora; phytophthora cinnamomi; Phytophthora: physiology; Plant; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: microbiology

Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª Ma; Abdelly, Chedly; Jorrín-novo, Jesús (Plant Physiology and Biochemistry, 2013)
Phytophthora cinnamomi is one of the agents that trigger the decline syndrome in Quercus spp., this being a serious threat to Mediterranean Holm oak forest sustainability and reforestation programs. Quercus ilex responses to Phytophthora cinnamomi have been studied in one-year olds seedlings from two Andalucía provenances, assessing the physiological water status and photosynthesis-related parameters. Upon inoculation with mycelium a reduction in water content, chlorophyll fluorescence, stomatal conductance and gas exchange was observed along a 90 days post inoculation period in both provenances. The reduction was higher in the most susceptible (SSA) provenance, than in the most tolerant (PCO), being these typical plant responses to drought stress. Leaf protein profiles were analyzed in non-inoculated and inoculated seedlings from the two provenances by using a 2-DE coupled to MS proteomics strategy. Ninety seven proteins changing in abundance in response to the inoculation were successfully identified after MALDI–TOF–TOF analyses. The largest group of variable identified proteins were chloroplasts ones, and they were involved in the photosynthesis, Calvin cycle and carbohydrate metabolism. It was noted that a general tendency was a decrease in the protein abundance as a consequence of the inoculation, being it less accused in the least susceptible, the Northern provenance (PCO), than in the most susceptible, the Southern provenance (SSA). This trend is clearly manifested in photosynthesis, amino acid metabolism and stress/defence proteins. On the contrary, some proteins related to starch biosynthesis, glycolysis and stress related peroxiredoxin showed an increase upon inoculation. These changes in protein abundance were correlated to the estimated physiological parameters and have been frequently observed in plants subjected to drought stress.
From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 23962806
Keywords: Gene Expression Regulation; Holm oak decline; Holm oak proteomics; Phytophthora; phytophthora cinnamomi; Phytophthora: physiology; Plant; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: microbiology

QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia (Plant Physiology and Biochemistry, 2013)
Abstract Cork oak is an economically important forest species showing a great tolerance to high temperatures and shortage of water. However, the mechanisms underlying this plasticity are still poorly understood. Among the stress regulators, transcription factors (TFs) are especially important since they can control a wide range of stress-inducible genes, which make them powerful targets for genetic engineering of stress tolerance. Here we evaluated the influence of increasing temperatures (up to 55 °C) or drought (18% field capacity, FC) on the expression profile of an R2R3-MYB transcription factor of cork oak, the QsMYB1. QsMYB1 was previously identified as being preferentially expressed in cork tissues and as having an associated alternative splicing mechanism, which results in two different transcripts (QsMYB1.1 and QsMYB1.2). Expression analysis by reverse transcription quantitative PCR (RT-qPCR) revealed that increasing temperatures led to a gradual down-regulation of QsMYB1 transcripts with more effect on QsMYB1.1 abundance. On the other hand, under drought condition, expression of QsMYB1 variants, mainly the QsMYB1.2, was transiently up-regulated shortly after the stress imposition. Recovery from each stress has also resulted in a differential response by both QsMYB1 transcripts. Several physiological and biochemical parameters (plant water status, chlorophyll fluorescence, lipid peroxidation and proline content) were determined in order to monitor the plant performance under stress and recovery. In conclusion, this report provides the first evidence that QsMYB1 TF may have a putative function in the regulatory network of cork oak response to heat and drought stresses and during plant recovery.
From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 24161757
Keywords: Abiotic stress; Adaptation; Cork oak; Droughts; Gene expression; Gene Expression Regulation; Genes; Hot Temperature; Physiological; Plant; Plant Bark; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; Recovery; RNA Splicing; Stress; Transcription Factors; Transcription Factors: genetics; Transcription Factors: metabolism; water

Genetic transformation of cork oak (Quercus suber L.) for herbicide resistance. - Alvarez, Rubén; Alvarez, José M; Humara, Jaime M; Revilla, Angeles; Ordás, Ricardo J (Biotechnology letters, 2009)
The bar gene was introduced into the cork oak genome. Cork oak embryogenic masses were transformed using the Agrobacterium strain AGL1 which carried the plasmid pBINUbiBar. This vector harbours the genes, nptII and bar, the latter under control of the maize ubiquitin promoter. The transgenic embryogenic lines were cryopreserved. Varying activities of phosphinothricin acetyl transferase were detected among the lines, which carried 1-4 copies of the insert. Molecular and biochemical assays confirmed the stability and expression of the transgenes 3 months after thawing the cultures. These results demonstrate genetic engineering of herbicide tolerance in Quercus spp.
Keywords: Acetyltransferases; Acetyltransferases: genetics; Acetyltransferases: metabolism; Gene Dosage; Genomic Instability; Herbicide Resistance; Herbicides; Herbicides: toxicity; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plants, Genetically Modified; Plants, Genetically Modified: drug effects; Plants, Genetically Modified: genetics; Plants, Genetically Modified: physiology; Plasmids; Promoter Regions, Genetic; Quercus; Quercus: drug effects; Quercus: genetics; Quercus: physiology; Rhizobium; Rhizobium: genetics; Transformation, Genetic; Zea mays; Zea mays: genetics

Genetic transformation of cork oak (Quercus suber L.) for herbicide resistance. - Alvarez, Rubén; Alvarez, José M.; Humara, Jaime M.; Revilla, Angeles; Ordás, Ricardo J. (Biotechnology letters, 2009)
The bar gene was introduced into the cork oak genome. Cork oak embryogenic masses were transformed using the Agrobacterium strain AGL1 which carried the plasmid pBINUbiBar. This vector harbours the genes, nptII and bar, the latter under control of the maize ubiquitin promoter. The transgenic embryogenic lines were cryopreserved. Varying activities of phosphinothricin acetyl transferase were detected among the lines, which carried 1-4 copies of the insert. Molecular and biochemical assays confirmed the stability and expression of the transgenes 3 months after thawing the cultures. These results demonstrate genetic engineering of herbicide tolerance in Quercus spp.
The following values have no corresponding Zotero field: accession-num: 19543858
Keywords: Acetyltransferases; Acetyltransferases: genetics; Acetyltransferases: metabolism; Gene Dosage; Genomic Instability; Herbicide Resistance; Herbicides; Herbicides: toxicity; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plants, Genetically Modified; Plants, Genetically Modified: drug effects; Plants, Genetically Modified: genetics; Plants, Genetically Modified: physiology; Plasmids; Promoter Regions, Genetic; Quercus; Quercus: drug effects; Quercus: genetics; Quercus: physiology; Rhizobium; Rhizobium: genetics; Transformation, Genetic; Zea mays; Zea mays: genetics

Proteomic analysis from haploid and diploid embryos of Quercus suber L. identifies qualitative and quantitative differential expression patterns. - Gómez, Aranzazu; López, Juan Antonio; Pintos, Beatriz; Camafeita, Emilio; Bueno, Ma Angeles (Proteomics, 2009)
Quercus suber L. is a Mediterranean forest species with ecological, social and economic value. Clonal propagation of Q. suber elite trees has been successfully obtained from in vitro-derived somatic and gametic embryos. These clonal lines play a main role in breeding and genetic studies of Q. suber. To aid in unravelling diverse genetic and biological unknowns, a proteomic approach is proposed. The proteomic analysis of Q. suber somatic and gametic in vitro culture-derived embryos, based on DIGE and MALDI-MS, has produced for the first time proteomic data on this species. Seventeen differentially expressed proteins have been identified which display significantly altered levels between gametic and somatic embryos. These proteins are involved in a variety of cellular processes, most of which had been neither previously associated with embryo development nor identified in the genus Quercus. Some of these proteins are involved in stress and pollen development and others play a role in the metabolism of tannins and phenylpropanoids, which represent two of the major pathways for the synthesis of cork chemical components. Furthermore, the augmented expression levels found for specific proteins are probably related to the homozygous state of a doubled-haploid sample. Proteins involved in synthesis of cork components can be detected at such early stages of development, showing the potential of the method to be useful in searching for biomarkers related to cork quality.
Keywords: cluster analysis; Cork oak; Diploidy; Electrophoresis; Embryonic Development; flow cytometry; Gametic embryogenesis; Gel; Haploid and diploid embryos; Haploidy; Plant Proteins; Plant Proteins: analysis; Plant Proteins: biosynthesis; Plant Proteins: genetics; Plant proteomics; Ploidies; Ploidy level; Principal component analysis; Proteomics; Proteomics: methods; Quercus; Quercus suber L.; Quercus: chemistry; Quercus: genetics; Quercus: metabolism; Seeds; Seeds: chemistry; Seeds: genetics; Seeds: metabolism; Two-Dimensional; Up-Regulation